2010
DOI: 10.1177/0011128710382342
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness of California’s Proposition 36 and Drug Court Programs Before and After Propensity Score Matching

Abstract: California’s voter-initiated Proposition 36 (Prop 36) program is often unfavorably compared to drug courts, but little is empirically known about the comparative effectiveness of the two approaches. Using statewide administrative data, analyses were conducted on all Prop 36 and drug court offenders with official records of arrest and drug treatment. Propensity score matching was used to create equivalent groups, enabling comparisons of success at treatment discharge, recidivism over 12 months post-treatment en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 58 publications
1
20
0
Order By: Relevance
“…23 Other studies have reported that Proposition 36 clients were more likely to have successfully completed treatment at discharge, but that recidivism after 12 months was higher relative to drug court referrals. 43 Similarly, clients receiving care from programs with a higher proportion of public funding and professionalization (staff members with graduate education) were more likely to achieve sobriety at discharge. These measures of program capacity are potentially critical to improving standards of care in substance abuse treatment 51 in the current health care reform environment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…23 Other studies have reported that Proposition 36 clients were more likely to have successfully completed treatment at discharge, but that recidivism after 12 months was higher relative to drug court referrals. 43 Similarly, clients receiving care from programs with a higher proportion of public funding and professionalization (staff members with graduate education) were more likely to achieve sobriety at discharge. These measures of program capacity are potentially critical to improving standards of care in substance abuse treatment 51 in the current health care reform environment.…”
Section: Discussionmentioning
confidence: 99%
“…41,42 In particular, in 2001 the state of California passed the Substance Abuse and Crime Prevention Act, known as Proposition 36, which permitted substance abuse treatment as an alternative to incarceration for drug offenders. In general, studies have found successful completion of treatment for participants of Proposition 36 programs when compared to self-referred individuals 23,43 and improved sobriety and crime-related outcomes for Proposition 36 participants when compared to individuals sentenced to incarceration. 43 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jurisdictional, or county-level, variation has been reported in SACPA program operations [8,[18][19][20][21][22][23][24][25], characteristics of participating offenders [18], and outcomes [26].…”
Section: Contextual Variationmentioning
confidence: 99%
“…Jurisdictional, or county-level, variation has been reported in SACPA program operations [8,[18][19][20][21][22][23][24][25], characteristics of participating offenders [18], and outcomes [26].The attitudes, training, and practices of key implementers impact the degree of success, or failure, of social policy initiatives [27], as does the nature of the linkages between cooperating agencies (i.e., exchanges of communication, trust, and resources) and the boundaries Methods: Administrative data were used to conduct multilevel, difference-in-differences analysis examining the effect of individual-and county-level variables on total service-utilization costs across eight domains over 30 months pre-and post-conviction.Results: County-level variability in the severity of offender populations served under SACPA and in the level of collaboration between SACPA stakeholders contributed to cost variability. More severe populations and less effective stakeholder communication produced increases in costs.…”
mentioning
confidence: 99%